‘That Mysterious People’: Jewish Merchants, Transparency, and Community in Mid-Nineteenth Century America - Olegario, R (1999)
In the mid-nineteenth century, American wholesalers began increasingly to rely on credit-reporting agencies to provide information about customers in distant localities. The demand for dependable information, coupled with the dynamism and competitiveness of the American market, helped usher into place a business culture that favored transparency and open networks. This article examines one group of merchants-immigrant Jews-whose traditions stood in contrast to the business elite's growing demand for disclosure.